Integrating climate security into policies: Roadmap for Yemen - Barry, Sinéad; McMurray, Spencer; Schmelzer, Nina (2024)
This roadmap aims to guide Yemeni policymakers in streamlining climate security consideration into policy and to highlight priorities for support to donors by providing short, medium, and long-term needs and requirements for mainstreaming. The roadmap considers the nation of Yemen as a whole and targets institutions within the internationally-recognised Government of Yemen.